2017
DOI: 10.1039/c7nj02858j
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent coordination polymers based on Ca2+ and octahedral cluster anions [{M6Cli8}Cla6]2− (M = Mo, W): synthesis and thermal stability studies

Abstract: Preparation of 1D coordination polymers based on luminescent hexanuclear cluster complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 51 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…They offer a vast compositional and structural diversity, and among all possible structures, the octahedral molybdenum cluster units [{Mo 6 X 8 }L 6 ] 2-(where X are inner halide ligands and L are apical anionic organic or inorganic ligands) have been the most investigated moieties, owing to their photophysical properties as well as their catalytic performances in water splitting. [1][2][3][4][5][6][7][8][9] Furthermore, in the broad context of nanoarchitectonics [10][11][12][13] 20 Nanoprecipitation by solvent shifting is the most straightforward strategy to obtain nanoparticles, widely used in pharmacy to produce nanoparticulate drugs. 21 The elaboration of nanocapsules is more challenging although it provides interesting opportunities resulting from their internal cavity, with potential applications in catalysis, photonics, enzyme protection or drug carriers.…”
mentioning
confidence: 99%
“…They offer a vast compositional and structural diversity, and among all possible structures, the octahedral molybdenum cluster units [{Mo 6 X 8 }L 6 ] 2-(where X are inner halide ligands and L are apical anionic organic or inorganic ligands) have been the most investigated moieties, owing to their photophysical properties as well as their catalytic performances in water splitting. [1][2][3][4][5][6][7][8][9] Furthermore, in the broad context of nanoarchitectonics [10][11][12][13] 20 Nanoprecipitation by solvent shifting is the most straightforward strategy to obtain nanoparticles, widely used in pharmacy to produce nanoparticulate drugs. 21 The elaboration of nanocapsules is more challenging although it provides interesting opportunities resulting from their internal cavity, with potential applications in catalysis, photonics, enzyme protection or drug carriers.…”
mentioning
confidence: 99%
“…On the basis of our broad experience with octahedral transition-metal cluster complexes, particularly, molybdenum clusters [{Mo 6 X 8 }­L 6 ] n (X = Cl, Br, or I; L = organic or inorganic ligands; Figure ), we suggest considering them as promising agents for photocatalytic water purification. Their variable terminal ligand (L) environment provides for chemical reactivity and solubility, while the highly stable cluster core {Mo 6 X 8 } 4+ is responsible for the photophysical properties, i.e., photoluminescence and the ability to generate reactive oxygen species (ROS), such as singlet oxygen, hydroxyl radical, superoxide radical, etc. ,, Owing to these beneficial characteristics, this class of compounds is already well-studied for numerous applications, including as components of optical waveguides, liquid-crystal devices, solar panels, antibacterial materials, , agents for bioimaging , and photodynamic therapy, ,,,, and catalysts. However, the water treatment processes employing hexamolybdenum cluster complexes remain little explored. To the best of our knowledge, the only two examples are the studies on rhodamine B (RhB) photodegradation in water using a [{Mo 6 Br 8 }­(N 3 ) 6 ] 2– cluster as a homogeneous catalyst or a heterogeneous one when combined with gold nanoparticles and graphene oxide as the support .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that although cyclic voltammetry data have been reported for many octahedral cluster complexes, only a few examples of 23-electron cluster complexes have been isolated as a single phase. These include [{Re 6 Q 8 }­(CN) 6 ] 3– (Q = S, Se, Te) and [{Re 6 Q 8 }­Y 6 ] 3– (Q = S, Se; Y = Cl, Br, I) compounds synthesized by chemical or electrochemical oxidation of the corresponding 24-electron parent cluster precursors, , and examples of 23e – tungsten cluster compounds, containing [{W 6 X 8 }­X 6 ] − (X = Br, I). In regards to molybdenum cluster complexes, compounds containing cluster anions [{Mo 6 X 8 }­Y 6 ] 2– (where X is an inner halogen ligand and Y is an outer organic or inorganic ligand) are well-known and have been extensively studied for the past half century, especially those based on [{Mo 6 Cl 8 }­Cl 6 ]. , In previous works, , it has been shown that complexes [{Mo 6 X 8 }­Y 6 ] 2– undergo quasi-reversible one-electron oxidation when X = Y = Cl or Br and irreversible oxidation when X = Y = I. Moreover, Gray et al succeded in generation of [{Mo 6 Cl 8 }­Cl 6 ] − in solution upon potentiostatic electrolysis, and noted that the ion is not stable in solution over time .…”
Section: Introductionmentioning
confidence: 99%